Increasing communication reliability in manufacturing environments - Radenkovic, Milena; Kostadinov, Ivaylo; Wietrzyk, Bartosz (2015)
This paper is concerned with low cost mechanisms that can increase reliability of machine to machine and machine to cloud communications in increasingly complex manufacturing environments that are prone to disconnections and faults. We propose a novel distributed and cooperative sensing framework that supports localized real time predictive analytics of connectivity patterns and detection of a range of faults together with issuing of notifications and responding on demand queries. We show that our Fault and Disconnection Aware Smart Sensing (FDASS) framework achieves significantly lower packet loss rates and communication delays in the face of unreliable nodes and networks when compared to the state of the art and benchmark approaches.